Representation Family Communication Pattern Digital Era in The Mitchells Vs. The Machines Film - Hayya Shofia (Universitas Bunda Mulia, 2023)
In this digital era, family disharmony occurs because each family is busy with its gadgets which creates solar or homo-solitarius humans (Prasanti, 2016). Children become digital natives, and adults become digital immigrants. Family communication is important. Family is the smallest part of people's life. Because of that, a harmonious society can be achieved starting from the life of harmonious families. This study discusses The Mitchells Vs. The Machines which represents the pattern of family communication in the digital era using Charles Sanders Pierce's semiotic analysis. In this film there is also have value of family communication which is the moral message of the solution to family conflict in the film.Â